Development of portable dc voltage calibrators with additive offsets adjusting - Matviiv, Roman; Yatsuk, Yurii; Yatsuk, Vasyl (Eastern-European Journal of Enterprise Technologies, 2018)
Improvement of portable equipment for controlling the DC voltage measuring channels of cyber-physical systems at the operating sites is proposed. Additive offsets and drifts make a dominant contribution to the error of portable DC voltage calibrators. Automatic correction based on the method of double switching inversion provides the opportunity to increase the productivity of multichannel system voltage meters at the operating sites. It is shown that the additive offsets during the DC voltage reproduction, in addition to the equivalent offset voltages of the operational amplifiers, ADCs or DACs, are caused by common type noises and leakage currents through the isolation of the power supply units. In the developed structure of the DC voltage calibrator, it is proposed to use the method of double switching inversion with subsequent analog averaging of the output signal for the automatic correction of the additive offsets. The error analysis and simulation showed the principal possibility of the calibrator additive offsets correction to the values limited by the non-identity of parameters of the closed pairs of switches. The analysis of the results of experimental studies of the voltage calibrator layout showed the invariance of the reproduced voltages from the voltage value and the location of the simulator of the additive error component in the layout structure. The uncorrected error value in the manual mode did not exceed ±1 μV for all reproduced values of the output voltage of the layout. It has been experimentally shown that the minimum value of the uncorrected error lies at a switching frequency of about 1.2 kHz within ±5 μV. The developed scheme can be implemented in the basis of programmable systems on the chip, which significantly improves the metrological characteristics, reduces the cost and unifies portable voltage calibrators and DC resistance simulators.